Large-Scale Profiling of Saponins in Different Ecotypes of Medicago truncatula - Lei, Zhentian; Watson, Bonnie S.; Huhman, David; Yang, Dong Sik; Sumner, Lloyd W. (Frontiers in Plant Science, 2019)
1625 samples representing 201 Medicago truncatula ecotypes were analyzed using ultrahigh pressure liquid chromatography coupled to mass spectrometry (UHPLC-MS) to ascertain saponin profiles in different M. truncatula ecotypes and to provide data for a genome-wide association study and subsequent line selection for saponin biosynthesis. These ecotypes originated from 14 different Mediterranean countries, i.e., Algeria, Cyprus, France, Greece, Israel, Italy, Jordan, Libya, Morocco, Portugal, Tunisia, Turkey, Spain and Syria. The results revealed significant differences in the saponin content among the ecotypes. European ecotypes generally contained higher saponin content than African ecotypes (p<0.0001). This suggests that M. truncatula ecotypes modulate their secondary metabolism to adapt to their environments. Significant differences in saponin accumulation were also observed between the aerial and the root tissues of the same ecotypes (p < 0.0001). While some saponins were found to be present in both the aerial and root tissues, zanhic acid glycosides were found predominantly in the aerial tissues. Bayogenin and hederagenin glycosides were found mostly in roots. The differential spatially resolved accumulation of saponins suggests that saponins in the aerial and root tissues play different roles in plant fitness. Aerial saponins such as zanhic glycosides may act as animal feeding deterrent and root saponins may protect against soil microbes.